PARTISIPASI MASYARAKAT TERHADAP PENANGGULANGAN BANJIR DI KOTA BANJARMASIN - Muhammad Subhan; Wahyu Wahyu; Ermayn Erhaka; Meldia Septiana (EnviroScienteae, 2012)
Research on public participation in flood prevention in the City of Banjarmasin conducted in 5 districts in the City of Banjarmasin, consisting of: Banjarmasin West: 13.37 km ², Banjarmasin South: 20.18 km ², Middle Banjarmasin: 11.66 km ², East Banjarmasin: 11, 54 km ² and North Banjarmasin: 15.25 km ² in December 2010. The purpose of this study are 1) knowing participation in the City of Banjarmasin before the occurrence of flooding and 2) knowing participation in Banjarmasin city after the flood. This research was conducted using qualitative methods. From the research result shows that the participation of people of Banjarmasin before the flood in the form of mutual help clean up the environment, creation of drainage channels, as well as the construction of houses with stage system. Public participation Banjarmasin city after the flood indicated only by cleaning trash and mud that is all around their house to clean and pleasing to the eye again. Banjarmasin City government is expected through the relevant agencies to improve the dissemination and extension of the flooding to the community. Intensive counseling by using various media such as leaflets, tabloids, advertising in mass media and electronic and disseminate to the public would be petrified in improving the knowledge society will flood.